(untitled) (Malay Literature, 2025)
The role of the ruled class, as recorded in classical texts such as Sejarah Melayu (Malay Annals), is crucial for understanding the social and political structure of traditional Malay society. However, the narrative of Sejarah Melayu tends to focus largely on the ruling class and aristocracy, leading to the underrepresentation of the ruled class’s roles and contributions, thereby creating a significant knowledge gap. This study attempts to fill the said gap by focusing on social structures, encompassing the role of community within the stratified and underrepresented ruled class. The common people, slaves and foreigners constituted the three subdivisions of this broader community within the ruled class hierarchy. The ruled class was often considered as passive in the social hierarchy of traditional Malay society since they were beholden to the influence and authority of the ruling class. Therefore, the main objective of this study is to discuss the role of the ruled class, which was divided into distinct classes in the social hierarchy of Malacca society in strengthening social stability and contributing to the development of Malay economy and culture. By analysing the power dynamics between the government and the people, this study holistically assesses the impact of the ruled class on the development of Malay history and heritage. This study employs qualitative historical method and descriptive analysis to explain the ruled class’s role as a community that supported the continuity of the monarchy during the Malacca Malay Sultanate period. The research also examines aspects of social mobility, particularly within the subordinate class. The findings reveal that the ruled class not only complemented the ruling class, but also served as a valuable asset in maintaining the balance and stability of social and economic development during that era. Full text: PDF